Antibiotic Use and Outcomes in Children in the Emergency Department With Suspected Pneumonia - Lipshaw, Matthew J. (Pediatrics, 2020)
BACKGROUND AND OBJECTIVES: Antibiotic therapy is often prescribed for suspected community-acquired pneumonia (CAP) in children despite a lack of knowledge of causative pathogen. Our objective in this study was to investigate the association between antibiotic prescription and treatment failure in children with suspected CAP who are discharged from the hospital emergency department (ED). METHODS: We performed a prospective cohort study of children (ages 3 months–18 years) who were discharged from the ED with suspected CAP. The primary exposure was antibiotic receipt or prescription. The primary outcome was treatment failure (ie, hospitalization after being discharged from the ED, return visit with antibiotic initiation or change, or antibiotic change within 7–15 days from the ED visit). The secondary outcomes included parent-reported quality-of-life measures. Propensity score matching was used to limit potential bias attributable to treatment selection between children who did and did not receive an antibiotic prescription. RESULTS: Of 337 eligible children, 294 were matched on the basis of propensity score. There was no statistical difference in treatment failure between children who received antibiotics and those who did not (odds ratio 1.0; 95% confidence interval 0.45–2.2). There was no difference in the proportion of children with return visits with hospitalization (3.4% with antibiotics versus 3.4% without), initiation and/or change of antibiotics (4.8% vs 6.1%), or parent-reported quality-of-life measures. CONCLUSIONS: Among children with suspected CAP, the outcomes were not statistically different between those who did and did not receive an antibiotic prescription.